Politik Hukum Pengadilan HAM Ad Hoc dalam Penegakan HAM di Indonesia - Avivah Firisqi Leksono; Siti Fatimah; Muhammad Adib Alfarisi (Journal of Law, Society, and Islamic Civilization, 2025)
The Ad Hoc Human Rights Court was established under Law Number 26 of 2000 as a manifestation of the state’s responsibility to uphold justice for gross human rights violations in Indonesia. However, its effectiveness and judicial independence remain problematic due to the dominance of political interests. This study aims to analyze the legal politics of the Ad Hoc Human Rights Court through three dimensions: Ius Constitutum, Ius Operatum, and Ius Constituendum. The research employs a normative legal method with a juridical approach by examining positive legal norms, legal principles, and political dynamics that influence the court’s implementation. The findings reveal that in the Ius Constitutum dimension, the establishment mechanism requiring the approval of the House of Representatives (DPR) upon the President’s proposal opens room for political intervention and weakens judicial independence. In the Ius Operatum dimension, the court’s implementation shows low effectiveness due to weak evidentiary procedures, limited application of the command responsibility principle, and strong political interference. Meanwhile, the Ius Constituendum dimension highlights the need for legal and political reforms through regulatory revisions, institutional strengthening, and the creation of an independent mechanism to ensure substantive justice. Therefore, the legal politics of the Ad Hoc Human Rights Court remain elitist and symbolic, necessitating a reorientation to strengthen accountability, judicial independence, and the protection of victims’ rights in cases of gross human rights violations.